Rac and roll over the corpses. - Caron, E. (Current Biology, 2000)
A genetic pathway controlling the removal of apoptotic corpses has now been identified in the nematode. Mammalian homologs of the components of this pathway are already known to have key roles in cell motility and integrin-mediated signaling, suggesting that the three processes are mechanistically related.